MOLDOVA-GUAM - PINZAR, Svetlana (CENTRAL ASIA AND THE CAUCASUS, 2008)
In today’s world, where regional cooperation is an inalienable part of interstate relations, associative diplomacy is becoming an increasingly popular and high-priority focus of attention. This phenomenon took root in the system of international relations during the postwar era, but it was not until transnational regional organizations underwent further multifunctional development that the concept “associative or group diplomacy” was introduced into scientific circulation in the mid-1990s. This definition can be found in the works of well-known researcher of diplomacy R. Barston, who believes that a special place is occupied in today’s diplomacy system by relations both among states within the framework of international regional organizations and among various regional groups and associations, as well as between states, on the one hand, and transnational regional organizations, on the other. In so doing, in the second case, the states should not be members of the international regional organization in question.1R. Barston singles out four traits that make it possible for us to talk about associative diplomacy as a separate form of multilateralization:written arrangements (agreements, contracts, cooperation programs);periodical meetings between the leaders of partner states (consultations, summits, negotiations, and so on).coordinated policy and joint activities.drawn-up and officially approved systems and mechanisms of interaction between the sides (granting loans, carrying out commercial exchanges, rendering technical assistance, implementing joint projects, and others).2All of these traits feature in diplomacy within the framework of GUAM, which makes it possible for us to describe this cooperation as group, or associative diplomacy.In this article, we will look at issues relating to Moldova’s participation in the establishment and development of GUAM as a regional association; we will try to show Moldova’s role and place in this process; and we will analyze its associative diplomacy from the viewpoint of methods, means, and specific actions. Special attention will be given to the goals and tasks the country sets while cooperating within the framework of the regional organization GUAM.Today, GUAM is a regional union which was institutionally registered as an international organization in May 2006. This took place at the summit in Kiev, where the structure acquired its official name—Organization for Democracy and Economic Development—GUAM. We will also note that prior to this meeting, Moldova chaired in GUAM and was extremely instrumental in helping this organization to transform into a full-fledged international transnational organization.It is also important to note that Moldovan President Vladimir Voronin was the first to suggest a name for this structure. He proposed calling it the Commonwealth of European Choice for Democracy and Economic Development, but this proposal was not adequately supported by those gathered at the summit. Nevertheless, this does not mean that the Organization members rejected or reject the idea of European integration, which the Moldovan leadership has been focusing great attention on in the past few years.